Rancanangan Model Usaha Berbasis Lingkungan Produk Paving Block dari Sampah Plastik (IJM: Journal of Multidisiplinary, 2025)
The processing of plastic waste into paving blocks has emerged as an alternative building material that is not only environmentally friendly. This study aims to design an environmentally based business model utilizing plastic waste as raw material for paving blocks, while also analyzing its technical, social, and economic potential through a literature review approach. The research method employed is descriptive qualitative, involving the analysis of various scientific literatures, research findings, and documentation from relevant community service activities. The findings indicate that plastic-based paving blocks possess technical characteristics that meet Indonesian National Standards (SNI) for light use applications, with a compressive strength of 180–200 kg/cm² and a water absorption rate of less than 6%. Economically, the low production cost and competitive selling price suggest a promising business prospect. Through the application of Business Model Canvas and SWOT analysis, a robust business framework was identified, supported by the abundance of raw materials, a simple production process, and growing market demand for sustainable products. Plastic waste paving blocks are therefore considered feasible to be developed as a practical and sustainable form of environmentally based entrepreneurship, with the potential to economically and socially empower communities.